Multi-institutional comparison of computer-based independent dose calculation for intensity modulated radiation therapy and volumetric modulated arc therapy. (January 2018) - Kamima, Tatsuya; Baba, Hiromi; Takahashi, Ryo; Yamashita, Mikiko; Sugawara, Yasuharu; Kawai, Daisuke; Yamamoto, Toshijiro; Satou, Aya; Tachibana, Hidenobu
Highlights: This is the first multicenter study of independent dose calculation for IMRT/VMAT. 477 clinically approved IMRT/VMAT prostate and head and neck plans were assessed. This study will help each institution to establish action levels. Feasible action levels can be set within ±5% for IMRT/VMAT. Care is needed for MLC modeling for leaf gap and transmission factors. Abstract: Purpose: No multi-institutional studies of computer-based independent dose calculation have addressed the discrepancies among radiotherapy treatment planning systems (TPSs) and the verification programs for intensity modulated radiation therapy (IMRT) and volumetric modulated arc therapy (VMAT). We conducted a multi-institutional study to investigate whether ±5% is a reasonable action level for independent dose calculation for IMRT/VMAT. Methods: In total, 477 IMRT/VMAT plans for prostate or head and neck (H&N) malignancies were retrospectively analyzed using a modified Clarkson-based commercial verification program. The doses from the TPSs and verification programs were compared using the mean ±1 standard deviation (SD). Results: In the TPS-calculated dose comparisons for prostate and H&N malignancies, the sliding window (SW) technique (−2.5 ± 1.8% and −5.3 ± 2.6%) showed greater negative systematic differences than the step-and-shoot (S&S) technique (−0.3 ± 2.2% and −0.8 ± 2.2%). The VMAT dose differences for prostate and H&N malignancies were 0.9 ± 1.8% and 1.1 ± 3.3%, respectively. The SDs were larger for the H&N plans than for the prostate plans in both IMRT and VMAT. Such plans including more out-of-field control points showed greater systematic differences and SDs. Conclusions: This study will help individual institutions to establish an action level for agreement between primary calculations and verification for IMRT/VMAT. A local dose difference of ±5% at a point within the planning target volume (above −350 HU) may be a reasonable action level.